Sikap Kekristenan terhadap Perang dan Perdamaian: Suatu Tinjauan Teologis Etis - Benyamin F Intan (Societas Dei: Jurnal Agama dan Masyarakat, 2022)
Looking at the relationship between war and religion, there are at least three popular ethical positions, namely holy war, pacifism, and just war. All three of them have their manifestations, both in Scripture and in church history,that rely on their logic, and produce their inadequacy. This article attempts to explore them in order  to give insight into Christian thinking about war. By using a normative ethical approach, this article concludes that the position of pacifism and Just War are the  options that can be taken. Furthermore, the two positions do not mutually negate each other but complementarily fill in the insufficiency of ethical questions about  war in the two ethical positions.